Maintenance Therapy Post-Hematopoietic Stem Cell Transplantation in Acute Myeloid Leukemia - Martina Canichella; Matteo Molica; Carla Mazzone; Paolo de Fabritiis (Current Oncology, 2024)
High-risk acute myeloid leukemia has been associated with a poor outcome. Hematopoietic stem cell transplantation (HSCT) represents the only curative option for eligible patients. Relapse after HSCT is a dramatic event with poor chances of survival. With the aim of reducing the rate of post-HSCT relapse, maintenance treatment has been investigated in this setting. Results from clinical trials suggest an advantage in the use of a maintenance strategy; however, standardized guidelines are not yet available due to the lack of prospective clinical trials. In this review, we have reported the most important strategies adopted as post-HSCT maintenance, highlighting their efficacy, but the current research also opens questions.